Cultivo de alta densidad en banano (Musa pararadisíaca Var. Cavendish)" - Tigasi Sigcha, Claudio Geovanny (2017)
The present research was carried out in the Experimental Center "La Playita", of the Technical University of Cotopaxi, in the province of Cotopaxi. (Geographic Location WGS 84: Latitude SO ° 56'27 "Length W 79 ° 13'25"). And a variable height of 193 masl. The objectives proposed were: To determine the efficiency in the high density planting of the banana crop var. Cavendish, at the La Playita Experimental Center, to evaluate the agronomic behavior of high density banana. They were distributed in the field in a random design, with a number of three treatments plus one control, with seven replicates and with a number of four experimental units. The variables that were evaluated were: plant height, total leaf number, number of functional leaves, diameter of the pseudostem. Fertilization was carried out with three doses: high with 2380 kg / ha-year, average dose 1700 kg / ha-year, low dose 1020 kg / ha-year one control. The results obtained were: 7 days after fertilization with 113.79 cm, at 14 days the highest value recorded the low dose with 124.32 cm. The highest number of leaves recorded the high dose with values of 7.36 leaves total, with medium and high doses obtained values of 7.36 and 7.14, while the control was shown below the other treatments with 6, 82. The stem diameter with higher values was obtained with the application of the low dose at 7 days, while at 14 days the best result was presented with the mean dose whose results were 17.31 while at 21 and 30 days the best result was presented with the middle dose treatment with 18.04 and 18.68 respectively.